Prevalence of Opportunistic Infection in Central Nervous System among Patients with HIV/AIDS at Dr. Hasan Sadikin General Hospital Bandung, Indonesia - Dinda Sayyidah Laela Fatimatuzzahra; Ahmad Rizal Ganiem; Aih Cahyani; Suryani Gunadharma; Sofiati Dian (Althea Medical Journal, 2022)
Background: The low coverage of diagnosis and treatment in patients with human immunodeficiency virus (HIV) infection in Indonesia increases the risk of opportunistic infections that affects various organs, including the central nervous system (CNS). This study aimed to determine the prevalence of opportunistic infections in the CNS among hospitalized patients with HIV/acquired immune deficiency syndrome (AIDS) at Dr. Hasan Sadikin General Hospital Bandung, Indonesia.Methods: In this cross-sectional study with a total sampling method, data were collected from HIV/AIDS patients who were diagnosed with CNS opportunistic infection and hospitalized in the neurology ward during the period 2015–2019. Data were presented as median (interquartile range) and percentage frequency.Results: Among the 2,606 HIV/AIDS patients registered, 219 (8.4%) were accompanied by CNS opportunistic infections. The highest number was cerebral toxoplasmosis (58.9%; n=129) followed by tuberculous meningitis (33.3%; n=73) and cryptococcal meningitis (7.8%; n=17). Most of the patients admitted for unconsciousness (64.4%; n=141), with unknown HIV-infection status (61.2%; n=134). Among patients with positive HIV-infection status, only 50.6% (43/85) patients were taking antiretroviral therapy (ART) and 24.7% (21/85) patients dropped out ART before being diagnosed with CNS opportunistic infections. The CD4+’s median value was 21 cells/mm3 (IQR 9-61.25), with mortality during hospitalization was 36.5% (80/219). Conclusions: The prevalence of CNS opportunistic infections among HIV-infected patients is 8.4%, dominated by cerebral toxoplasmosis, and laboratory result showed very low CD4+ levels. The diagnosis of HIV infection is shortly made before hospitalization, and those who has been diagnosed have low compliance with ART. The mortality rate during hospitalization is high.